Comparison of outcomes of different biopsy schedules among men on active surveillance for prostate cancer: An analysis of the G.A.P.3 global consortium database. Issue 7 (7th March 2022) - Beckmann, Kerri R.; Bangma, Chris H.; Helleman, Jozien; Bjartell, Anders; Carroll, Peter R.; Morgan, Todd; Nieboer, Daan; Santaolalla, Aida; Trock, Bruce J.; Valdagni, Riccardo; Roobol, Monique J.; ,
Abstract: Background: The optimal interval for repeat biopsy during active surveillance (AS) for prostate cancer is yet to be defined. This study examined whether risk of upgrading (to grade group ≥ 2) or risk of converting to treatment varied according to intensity of repeat biopsy using data from the GAP3 consortium's global AS database. Materials and Methods: Intensity of surveillance biopsy schedules was categorized according to centers' protocols: (a) Prostate Cancer Research International Active Surveillance project (PRIAS) protocols with biopsies at years 1, 4, and 7 (10 centers; 7532 men); (b) biennial biopsies, that is, every other year (8 centers; 4365 men); and (c) annual biopsy schedules (4 centers; 1602 men). Multivariable Cox regression was used to compare outcomes according to biopsy intensity. Results: Out of the 13, 508 eligible participants, 56% were managed according to PRIAS protocols (biopsies at years 1, 4, and 7), 32% via biennial biopsy, and 12% via annual biopsy. After adjusting for baseline characteristics, risk of converting to treatment was greater for those on annual compared with PRIAS biopsy schedules (hazard ratio [HR] = 1.66; 95% confidence interval [CI] = 1.51–1.83; p < 0.001), while risk of upgrading did not differ (HR = 0.96; 95% CI = 0.84–1.10). Conclusion: Results suggest more frequent biopsy schedules may deter some men from continuing AS despite no evidence of grade progression.